Current (Food) Allergenic Risk Assessment: Is It Fit for Novel Foods? Status Quo and Identification of Gaps. Issue 1 (11th December 2017) - Mazzucchelli, Gabriel; Holzhauser, Thomas; Cirkovic Velickovic, Tanja; Diaz‐Perales, Araceli; Molina, Elena; Roncada, Paola; Rodrigues, Pedro; Verhoeckx, Kitty; Hoffmann‐Sommergruber, Karin
Abstract: Food allergies are recognized as a global health concern. In order to protect allergic consumers from severe symptoms, allergenic risk assessment for well‐known foods and foods containing genetically modified ingredients is installed. However, population is steadily growing and there is a rising need to provide adequate protein‐based foods, including novel sources, not yet used for human consumption. In this context safety issues such as a potential increased allergenic risk need to be assessed before marketing novel food sources. Therefore, the established allergenic risk assessment for genetically modified organisms needs to be re‐evaluated for its applicability for risk assessment of novel food proteins. Two different scenarios of allergic sensitization have to be assessed. The first scenario is the presence of already known allergenic structures in novel foods. For this, a comparative assessment can be performed and the range of cross‐reactivity can be explored, while in the second scenario allergic reactions are observed toward so far novel allergenic structures and no reference material is available. This review summarizes the current analytical methods for allergenic risk assessment, highlighting the strengths and limitations of each method and discussing the gaps in this assessment that need to be addressed in the near future. Abstract : There is a rising need of additional novel food sources with adequate nutritional value and low health risk. Food allergic consumers develop adverse immune reactions toward nontoxic dietary proteins. Current allergenic‐risk assessment includes extraction and characterization of food proteins and immunological testing for their allergenic activity. The study summarizes the current analytical methods applied and the need for improved allergenic risk assessment for novel foods.